Writing for design professionals : a guide to writing successful proposals, letters, brochures, portfolios, reports, presentations, and job applications for architects, engineers, and interior designers - Kliment, Stephen A. (W.W. Norton, 1998)
Written and oral communication plays a vital role in advancing design professionals' careers. Stephen Kliment spells out the various forms of writing that professionals need, including marketing and promotional materials and reports and project communications with clients.